Effect of temperature on nitrogen removal and biological mechanism in an up-flow microaerobic sludge reactor treating wastewater rich in ammonium and lack in carbon source. (February 2019) - Meng, Jia; Li, Jiuling; Li, Jianzheng; Nan, Jun; Deng, Kaiwen; Antwi, Philip
Abstract: Previous study has demonstrated that microaerobic process is effective in nitrogen removal from the wastewater with high ammonium and low carbon to nitrogen ratio. In the microaerobic system, synergistic action of anammox, ammonia oxidizing bacteria (AOB), nitrite oxidizing bacteria (NOB) and denitrifiers was the key issues to remove nitrogen from the wastewater rich in ammonium. Temperature has a significant effect on specific growth rate and activity of various nitrogen removal functional bacteria. In this study, the effect of temperature (35 °C–15 °C) on nitrogen removal were investigated in an up-flow microaerobic sludge reactor (UMSR) at the HRT of 8 h and reflux ratio of 45. Above 71.2% of total nitrogen (TN) and 80.7% of NH4 + removal efficiencies were observed at the temperature no less than 17 °C. With the temperature further decreasing to 15 °C, denitrifiers still dominant the UMSR, but AOB, NOB and Candidatus Brocadia as the predominant anammox bacteria were inhibited revealed by high throughput sequencing, resulting in the decrease of TN and NH4 + removal to 39.7% and 61.8%, respectively. Fortunately, when the temperature rebounded to 20 °C, a higher TN and NH4 + removal of 81.2% and 97.3% were obtained again in the UMSR. Graphical abstract: Highlights: A lab-scale UMSR was constructed to treat wastewater with low C/N ratio. Above 71.2% of TN and 80.7% of NH4 + removal were reached at temperature >17 °C. Decrease in temperature inhibited AOB, NOB and anammox bacteria. TN and NH4 + removal can be recovered with temperature rebounding to 20 °C.